2013
DOI: 10.4317/jced.51104
|View full text |Cite
|
Sign up to set email alerts
|

The influence of topic and systemic administration of copaiba oil on the alveolar wound healing after tooth extraction in rats

Abstract: The Copaiba oil has been used as an auxiliary treatment of inflammations, skin disorders and stomach ulcers, however, in dentistry, this “alternative” medicine has not been investigated yet. The purpose of this study was to evaluate the influence of topic and systemic administration of copaiba oil on the alveolar wound healing after tooth extraction. Twenty-eight wistar male rats had their lower first molar teeth extracted. Subsequently, they were divided in four groups, according to the treatment performed: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
7
1
3
Order By: Relevance
“…We believe that the extract concentration might be pointed as a possible cause to the inefficacity of copaiba oil concerning wound healing observed herein. The antiinflammatory effects of copaiba appear to be enhanced by the systemic administration (Dias da Silva et al, ); thus, the administration route chosen by our group might also have contributed to the lack of effectiveness. We recognize the study design as a limitation that may have implied a lack of significant results.…”
Section: Resultsmentioning
confidence: 97%
“…We believe that the extract concentration might be pointed as a possible cause to the inefficacity of copaiba oil concerning wound healing observed herein. The antiinflammatory effects of copaiba appear to be enhanced by the systemic administration (Dias da Silva et al, ); thus, the administration route chosen by our group might also have contributed to the lack of effectiveness. We recognize the study design as a limitation that may have implied a lack of significant results.…”
Section: Resultsmentioning
confidence: 97%
“…Another study found an almost 100% microbial reduction after preparation with 20% ginger glycolic extract as auxiliary chemical substance, demonstrating high effectiveness against C. albicans, E. faecalis, and E. coli [9]. e oil of copaiba is brownish-yellow and has been shown to have anti-inflammatory, curative, analgesic, antibacterial, antifungal, and antitumor properties [32]. In the present study, copaiba only exhibited bacteriostatic activity against E. faecalis.…”
Section: Discussionmentioning
confidence: 43%
“…Although several authors have investigated the biological and therapeutic properties of Copaifera spp, such as antifungal, antileishmanial, alveolar wound healing after tooth extraction in rats, anti-inflammatory, antioxidant, antimutagenic and others [23][24][25][26], our data exhibited the immunomodulatory action of Copaifera oleoresins.…”
Section: Discussionmentioning
confidence: 43%